Multilingual Code Mixing in Sasak Language in Karang Buyuk Ampenan - Danul Aristiawan (Universitas Pendidikan Mandalika, 2018)
This research aimed at analyzing and describing the use of multilingual code mixing as one of communication tool specially conducted in Karang Buyuk, Ampenan. Multilingual Code Mixing used by the people in Karang Buyuk, Ampenan in daily conversation and communication among sasak community and other community, people in Karang Buyuk, Ampenan want to show their solidarity and their prestige in society. The method which was applied in this research was a descriptive qualitative approach) in this case the writer use ethnograpy method. The data being analyzed are descriptive data in form of written words and sentences. The writer used some observation and also interview to collect data and he record the data. Based on the recording, he makes the transcrip and analysis the data. He seperated the data based on some criteria such as education level, age, gender, occupation, topic, and situation. This criteria used by the writer to analysis the data resources, and answer the research question. Based on the data results of the analysis, some of the important research finding are stated as follows; Firts people in Karang Buyuk, Ampenan are varied on some aspects, such as education level, age, occupation, situation and any other aspect that influence the language. Second, the poeple use code mixing among the sasak people is to show their prestige in the society, and they are proud in using code mixing, and if they make the conversation with different ethnic group the people in Karang Buyuk want to show their solidarity and to avoid the interethnic conflict among the society